Auditoría administrativa y su relación con la toma de decisiones de la empresa municipal de agua potable y alcantarillado del gobierno autónomo descentralizado del cantón Valencia, año 2014 - Cuyo Ilaquiche, Manuel Rodrigo (2016)
This research was conducted in the Municipal Water and Sewerage GAD of Valencia Canton, located in Los Rios, Valencia Av. December 13 s / n y Cruz Herrera, who provides potable water and sewerage approximately 2500 Valencian families; is a company that operates with funding from the central government to ensure access to vital liquid to the cantonal head, and urban parishes La Union and New Union, covering the period from January 1 to December 31, 2014, the goal is to develop a Management Audit and their relation to decision making EMAPAV, Valencia Canton, 2014. The theoretical foundation period adjusted to the subject of research supports the audit process. Research methodology by physical and objective information was obtained; applying methods and assessment tools it could conduct the interview to Manager and know important aspects within the administration. For the audit process COSO I which showed acceptable results having a confidence level of 81.58%, a risk level of 18.42% and audit risk is 2.50% was used. In research it is concluded that the analysis applied to the Annual Operating Plan Survey revealed inadequate implementation of procedures which in turn allow improper administration, regarding the evaluation of internal control allowed determining compliance with the standards applied in EMAPAV, the identifying indicators of efficiency and effectiveness agreed to meet compliance with the implementation of the programmed budget, determining that in the mission area drinking water meets 88% while in the Sewer meets 77% and personnel training with 24% compliance.